Cross-scale manufacturing method of porous flexible piezoresistive sensor with designable structure
By combining the indirect 3D printing process of soluble photosensitive resin and the porous flexible polymer molding process of water templates, the mismatch problem between the process and materials in cross-scale manufacturing is solved, and high-precision and high-quality complex three-dimensional structure molding is achieved, improving the improvement of high-quality The performance and application adaptability of porous flexible piezoresistive sensors.
Patent Information
- Application Number
- CN202411840301.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-18
AI Technical Summary
In the cross-scale manufacturing of existing porous flexible piezoresistive sensors, there are problems that difficult to match between processes and materials, resulting in low structural molding accuracy and insufficient structural designability, which limits the improvement of sensor performance.
Indirect 3D printing process using soluble photosensitive resin is combined with water template porous flexible polymer molding process, and the dependence on material forming ability is reduced through indirect 3D printing, achieving high-precision, high-quality complex three-dimensional structural molding.
It realizes the formation of a complex three-dimensional structure with strong structural designability. The porous flexible piezoresistive sensor has the characteristics of high sensitivity, wide stress response range, ultra-elastic, lightweight, flexible and breathable, which improves the sensor. performance and application scenario adaptability.
Smart Images

Figure CN119469490A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of porous flexible piezoresistive sensors, and in particular relates to a cross-scale manufacturing method of a porous flexible piezoresistive sensor with a designable structure. Background Art
[0002] With the development of intelligent electronic devices, research on wearable flexible pressure sensors that can realize human-computer interaction has attracted much attention. Wearable flexible pressure sensors can be used to manufacture human electronic skin and realize real-time monitoring and feedback of human health, which has great research and application value. Flexible piezoresistive sensors have attracted much attention due to their high sensitivity to strain, fast response speed, relatively simple structure and durability.
[0003] Polydimethylsiloxane (PDMS) is widely used as the dielectric layer of piezoresistive pressure sensors due to its flexibility, low elastic modulus and thermal stability. In order to improve the sensitivity and stress detection range of piezoresistive sensors, the preparation of porous structures is an effective solution. The porous structure gives piezoresistive sensors the advantages of high sensitivity, light weight and high compressibility. However, the current research on porous piezoresistive sensors is limited to the molding and manufacturing of a single porous structure, which makes it difficult to take into account both high sensitivity and a large stress measurement range. At the same time, the relevant preparation processes generally have weak manufacturing capabilities, strong randomness, and insufficient complex structure molding capabilities, resulting in insufficient structural designability of porous piezoresistive sensors. How to achieve the designable structural molding and manufacturing of porous piezoresistive sensors is a problem that must be solved to further improve the sensing performance of porous piezoresistive sensors.
[0004] Additive manufacturing technology can produce precisely customized structures from micro to macro scales, thus realizing various carefully designed structures. Therefore, it is expected that the designable structural molding of porous piezoresistive sensors can be realized with the help of additive manufacturing technology. However, the designable structural molding of porous flexible piezoresistive sensors involves cross-scale structural molding. At present, cross-scale manufacturing faces problems such as the difficulty in matching between processes and between processes and materials. This is mainly reflected in the difficulty of directly and simply combining the porous structure preparation process and 3D printing technology, and the poor controllability of the printing slurry material due to the high requirements of 3D printing on the material molding ability. At the same time, due to the involvement of multi-scale structural molding, the difficulty of structural molding is greatly increased, which will cause problems such as poor manufacturing quality, low molding accuracy, and weak structural designability. It is often difficult to take into account the structural integrity of each scale at the same time. The multi-scale structure has low structural complexity, which greatly limits the improvement of the performance of flexible sensors by structural design.
[0005] Chinese patent CN115232355 discloses a method for preparing hierarchical porous PDMS based on a soft template and its application in sensors. The patent prepares PDMS with hierarchical porosity by mixing PVA-B hydrogel and PDMS solution and then curing and drying. The method realizes the molding of hierarchical porous structure and can effectively improve the sensing performance of the sensor. However, the multi-level structure prepared by this method is still limited to random porous molding, and the structural design and control capabilities at various scales are weak. The excessive randomness of structural molding leads to its weak structural designability, which hinders the further improvement of sensor performance.
[0006] Chinese patent CN115386131A discloses a porous nanocomposite material for self-powered and self-sensing flexible electronic devices, and its preparation method and application. In the preparation method, granulated sugar is used as a sacrificial template to prepare a granulated sugar-CNTs template, and then a PDMS polymer is added, and the granulated sugar is dissolved after curing to prepare a PDMS-CNTs porous structure. This method also has the problem of a single molding structure scale, and because it uses granulated sugar as a template, the solid template will severely limit the fluidity of the mixture after adding the PDMS polymer, making it difficult to use the mixture for further structural molding and manufacturing. The structural designability is seriously insufficient, and only the manufacture of bulk porous structures can be achieved. The prepared flexible piezoresistive sensor has insufficient sensing performance and poor structural designability, and is difficult to adapt to complex application scenarios.
[0007] Chinese patent CN114211744A provides a 3D printed self-filling multi-layer porous sensor and a preparation method thereof. The patent mixes PDMS, a curing agent, water and a conductive functional filler as a printing slurry, and uses a 3D printing process to print a dot matrix structure. Due to the introduction of 3D printing technology, the molding and manufacturing capabilities of the sensor's three-dimensional structure are improved, and the designability and complexity of the sensor structure are improved. The sensor's sensing performance can be further improved by structural design. However, since this method is still limited to the idea of direct 3D printing, it is difficult to avoid the restrictive relationship between the process and the material. It is not only difficult to adjust the water content of the PDMS after curing to achieve the regulation of the porosity of the porous structure, but it is even more difficult to achieve the molding of the porous structure under high porosity, which leads to the fact that the sensitivity of the sensor prepared by this method still has a lot of room for improvement; at the same time, it is worth noting that the structural molding accuracy of the method of this patent is insufficient, which is much greater than 500μm. The direct 3D printing method will find it difficult to avoid the limitations of the direct 3D printing process on the printing slurry, and it is very easy to have a mismatch between the process and the material. Not only is it difficult to adjust the printing slurry such as water content and conductive filler, but the printing slurry will also seriously limit the molding quality and molding ability of the structure, and thus affect the sensor's sensing performance and adaptability to application scenarios.
[0008] In summary, existing cross-scale manufacturing faces problems such as difficulty in matching processes, processes and materials, and mutual constraints between materials and molding processes, which limits the design and manufacturability of multi-level structures of sensors, and further limits the further improvement of the performance of flexible piezoresistive sensors. Summary of the invention
[0009] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a cross-scale manufacturing method for a structurally designable porous flexible piezoresistive sensor, which avoids the mismatch problem between processes and processes and between processes and materials that is very easy to occur in cross-scale manufacturing, and can achieve high-precision, high-quality complex three-dimensional structure molding with strong structural designability. The prepared structured porous flexible piezoresistive sensor has the characteristics of high sensitivity, wide stress response range, superelasticity, light weight, flexibility, good air permeability, etc.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is:
[0011] A cross-scale manufacturing method for a porous flexible piezoresistive sensor with a designable structure comprises the following steps:
[0012] The first step is to disperse the conductive filler in the flexible polymer phase: add a surfactant to an organic solvent and stir to dissolve it, with a mass fraction of 1%-20%, disperse the conductive filler in the organic solvent, with a mass fraction of 0.5%-10%, use a cell disruptor to evenly disperse the conductive filler in the organic solvent, and then mix the organic solvent dispersed with the conductive filler with the flexible polymer in a mass ratio of 1:2 to 2:1, heat in a water bath and stir with a magnetic stirrer to fully mix them, and dry the organic solvent to obtain a flexible polymer dispersed with the conductive filler;
[0013] Step 2, preparation of a flexible polymer-water emulsion: adding a flexible polymer curing agent to the flexible polymer dispersed with a conductive filler prepared in the first step and stirring to fully mix, then slowly adding deionized water to the flexible polymer and stirring to fully obtain a uniform flexible polymer-water emulsion;
[0014] The third step is to prepare the soluble photosensitive resin mold: pour the soluble photosensitive resin into the resin tank of the light-curing 3D printer, adjust the position of the printing work platform and the release film until the light machine is fully focused, set the process parameters of 3D printing layer thickness, exposure time and light intensity on the 3D printer host, and use ultraviolet light exposure to realize the layer-by-layer curing and stacking of the resin mold to prepare a soluble photosensitive resin mold with a structural design;
[0015] Step 4, preparation of a paraffin mold: placing a paraffin block into a first container, placing the first container into a vacuum oven and heating it until the paraffin is completely melted, then placing the soluble photosensitive resin mold prepared in the third step into the melted paraffin until the paraffin completely immerses the soluble photosensitive resin mold, then evacuating the container so that the paraffin can completely wrap the soluble photosensitive resin mold, and cooling the container until the paraffin is completely cooled and solidified;
[0016] Step 5, removing the soluble photosensitive resin: placing the paraffin mold wrapped with the soluble photosensitive resin mold prepared in step 4 into an alkaline solution until the photosensitive resin is completely dissolved in the alkaline solution, and using a liquid convection device to assist in dissolving the photosensitive resin;
[0017] Step 6, pouring the flexible polymer-water emulsion into the paraffin mold: placing the paraffin mold obtained in the fifth step into the flexible polymer-water emulsion prepared in the second step, so that the emulsion completely immerses the paraffin mold, evacuates to remove the residual air in the emulsion, and leaves it to stand until the emulsion is completely poured into the paraffin mold;
[0018] Step 7, curing of the flexible polymer-water emulsion: placing the paraffin mold filled with the flexible polymer-water emulsion obtained in step 6 into an oven for curing so that the flexible polymer is completely cross-linked and solidified;
[0019] Step 8, removing the paraffin mold: placing the structured flexible polymer wrapped with paraffin prepared in step 7 into a second container filled with water, and placing the second container in a water bath to keep it warm, and utilizing the principle that paraffin melts at high temperature and separates from water to remove the paraffin from the structured flexible polymer with high water content, thereby obtaining a structured flexible polymer with a specific designed structure;
[0020] Step 9, preparation of structured flexible polymer porous structure: placing the structured flexible polymer prepared in step 8 into an oven and drying at high temperature until the water in the structured flexible polymer is completely evaporated and the total mass remains unchanged;
[0021] Step 10. Preparation of flexible piezoresistive sensor: evenly spin-coat conductive silver paste as electrodes on the flexible substrate, and then adhere two electrodes to both sides of the structured flexible polymer porous structure prepared in step 9, heat and cure, to form a flexible piezoresistive sensor.
[0022] In the first step, the flexible polymer material is polydimethylsiloxane (PDMS).
[0023] In the first step, the organic solvent is one or more of anhydrous ethanol, tert-butyl alcohol, isopropanol, n-hexane and toluene.
[0024] In the first step, the conductive filler is one or more of carbon nanotubes, carbon nanosheets, MXene, and graphene; when carbon nanotubes are used, long-walled multi-walled carbon nanotubes with a length of 10-30 μm, an inner diameter of 5-10 nm, and an outer diameter of 20-30 nm are used.
[0025] In the first step, the surfactant is one or more of sodium dodecyl sulfate (SDS), benzalkonium chloride (BKC), Triton X-100 (TX-100), dimethylsiloxane ethylene oxide block copolymer (DBE-621), and Span80.
[0026] The method for slowly adding water to the flexible polymer in the second step is: slowly adding small doses to the flexible polymer uniformly dispersed with conductive fillers prepared in the first step, and using a planetary centrifugal mixer to stir for 1-2 minutes after each addition of water. After all the water is added to the flexible polymer, use a planetary centrifugal mixer to stir for 15-25 minutes to fully mix the flexible polymer and water to obtain a stable flexible polymer-water emulsion.
[0027] When the flexible polymer is mixed with deionized water in the second step, the weight proportion of the deionized water is 10% to 70%.
[0028] When a planetary centrifugal mixer is used for stirring in the second step, the speed setting range is 200 rpm to 2000 rpm.
[0029] When water is added gradually in small doses, the single added amount shall not exceed 10% of the total mass of the flexible polymer.
[0030] In the fifth step, the alkali solution is one or both of KOH solution and NaOH solution.
[0031] In the fifth step, the liquid convection device is a small water pump or a similar device.
[0032] When the flexible polymer-water emulsion is heated in the seventh step to crosslink and solidify it, the oven temperature should be set below 60°C.
[0033] In the eighth step, the temperature setting of the water bath for heat preservation should be higher than 65°C and lower than 100°C.
[0034] In the ninth step, the temperature setting of using an oven to dry the moisture in the structured flexible polymer at high temperature should be higher than 100°C.
[0035] The minimum structural rod diameter of the structured flexible polymer porous structure prepared in the ninth step reaches 150 μm.
[0036] Compared with the prior art, the advantages and positive effects of the present invention are:
[0037] The present invention combines the indirect 3D printing process of soluble photosensitive resin with the water template porous flexible polymer molding process, and proposes a cross-scale manufacturing method for a porous flexible piezoresistive sensor with a designable structure, which solves the mismatch problem between processes and processes and between processes and materials that is very easy to occur in cross-scale manufacturing, and can realize high-precision, high-quality complex three-dimensional structure molding, and the structure is highly designable. Due to the use of the indirect 3D printing process, the dependence on the material molding ability is greatly reduced, and the manufacturing of complex porous three-dimensional structures with a minimum rod diameter of 150μm can be realized, and the three-dimensional structure molding of complex structures such as lattice structures, octagonal trusses and diamonds can be realized. And because water is used as a porous template, a large number of microporous structures can be further introduced into the formed complex three-dimensional structure. A large number of microporous structures can not only further improve the flexibility and lightweight of the sensor, but also greatly improve the sensitivity of the sensor because the micropores are more sensitive to stress. The prepared porous flexible piezoresistive sensor has the characteristics of flexibility, lightness, superelasticity, high sensitivity and wide response range, which greatly improves the sensing performance and application scenario adaptability of the flexible piezoresistive sensor as a wearable device. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The figure is a flow chart of an embodiment of the present invention.
[0039] Figure 2 This is a SEM image of the structured porous polymer according to an embodiment of the present invention.
[0040] Figure 3 This is a SEM image of a single rod diameter of a structured porous flexible polymer according to an embodiment of the present invention.
[0041] Figure 4 CNTs are uniformly dispersed on the pore walls of the porous polymer in the embodiment of the present invention.
[0042] Figure 5 It is the piezoresistive sensing signal of the structured porous flexible piezoresistive sensor according to an embodiment of the present invention. DETAILED DESCRIPTION
[0043] The present invention is described in detail below in conjunction with embodiments and drawings.
[0044] Reference Figure 1 , a cross-scale manufacturing method of a porous flexible piezoresistive sensor with a designable structure, comprising the following steps:
[0045] The first step is to disperse the conductive filler in the flexible polymer phase: add the surfactant to the organic solvent and stir to dissolve, the mass fraction is 1%-20%, and stir with a magnetic stirrer for 10 minutes to fully mix, disperse the conductive filler in the organic solvent, the mass fraction is 0.5%-10%, use a cell disruptor to evenly disperse the conductive filler in the organic solvent, and then mix the organic solvent dispersed with the conductive filler with the flexible polymer, the mass ratio of the two when mixed is between 1:2 and 2:1, heat in a water bath and stir with a magnetic stirrer for 120 minutes to fully mix, and dry the organic solvent to obtain a flexible polymer dispersed with the conductive filler;
[0046] The flexible polymer material is polydimethylsiloxane (PDMS); the organic solvent is one or more of anhydrous ethanol, tert-butyl alcohol, isopropanol, n-hexane, and toluene; the conductive filler is one or more of carbon nanotubes, carbon nanosheets, MXene, and graphene. When carbon nanotubes are used, long-walled multi-walled carbon nanotubes with a length of 10-30 μm, an inner diameter of 5-10 nm, and an outer diameter of 20-30 nm are preferred; the surfactant is one or more of sodium dodecyl sulfate (SDS), benzalkonium chloride (BKC), Triton X-100 (TX-100), dimethylsiloxane ethylene oxide block copolymer (DBE-621), and Span80;
[0047] The second step is the preparation of a flexible polymer-water emulsion: the flexible polymer and its curing agent are mixed in a mass ratio of 10:1, and stirred with a magnetic stirrer for 10 minutes to fully mix them; then deionized water is slowly added to the flexible polymer, and stirred with a planetary centrifugal stirrer to obtain a uniform flexible polymer-water emulsion;
[0048] The method of slowly adding water to the flexible polymer is as follows: slowly adding small amounts of water to the flexible polymer uniformly dispersed with the conductive filler prepared in the first step, and stirring for 1 minute using a planetary centrifugal mixer after each addition of water. After all the water is added to the flexible polymer, stirring for 20 minutes using a planetary centrifugal mixer to fully mix the flexible polymer and water to obtain a stable flexible polymer-water emulsion;
[0049] When the flexible polymer is mixed with deionized water, the mass proportion of the deionized water is between 10% and 70%, and in this embodiment is 50%;
[0050] When using a planetary centrifugal mixer for stirring, the speed setting range is 200 rpm to 2000 rpm, and in this embodiment it is 800 rpm;
[0051] When water is added in small doses gradually, the single drop amount shall not exceed 10% of the total mass of the flexible polymer. In this embodiment, the single drop amount is 5% of the total mass of the flexible polymer.
[0052] The third step is to prepare the soluble photosensitive resin template: pour the soluble photosensitive resin into the resin tank of the light-curing 3D printer, cover it with a release film, adjust the position of the printing work platform and the release film until the light machine is fully focused, set the layer thickness of 3D printing to 50μm, the single exposure time to 12 seconds, and the light intensity to 55I on the 3D printer host, and use ultraviolet light exposure to realize the layer-by-layer curing and stacking of the resin mold to prepare a soluble photosensitive resin mold with a structural design;
[0053] Step 4, preparation of paraffin mold: put the paraffin block into a beaker, put the beaker into a vacuum oven and heat it until the paraffin is completely melted, then put the soluble photosensitive resin mold prepared in the third step into the melted paraffin until the paraffin completely immerses the photosensitive resin mold, then evacuate for 20 minutes so that the paraffin can completely wrap the soluble photosensitive resin mold, then take it out and cool it until the paraffin is completely cooled and solidified;
[0054] Step 5, removing the soluble photosensitive resin: placing the paraffin mold wrapped with the soluble photosensitive resin mold prepared in step 4 into an alkali solution with a concentration of 1 mol / L until the photosensitive resin is completely dissolved in the alkali solution, and using a liquid convection device to assist the resin dissolution;
[0055] The alkali solution is one or both of KOH solution and NaOH solution; the liquid convection device is a small water pump or similar device;
[0056] Step 6, pouring the flexible polymer-water emulsion into the paraffin mold: placing the paraffin mold prepared in the fifth step into the flexible polymer-water emulsion prepared in the second step, so that the emulsion completely immerses the paraffin mold, evacuates for 10 minutes to remove the residual air in the emulsion, and stands until the emulsion is completely poured into the paraffin mold;
[0057] Step 7, curing of the flexible polymer-water emulsion: placing the paraffin mold filled with the flexible polymer-water emulsion obtained in step 6 in an oven for curing for 48 hours to completely crosslink and solidify the flexible polymer;
[0058] When the flexible polymer-water emulsion is heated to make it cross-linked and solidified, the oven temperature should be set below 60° C., and the temperature in this embodiment is set to 50° C.;
[0059] Step 8, removing the paraffin mold: placing the structured flexible polymer wrapped with paraffin prepared in step 7 into a beaker filled with water, and placing the beaker in a water bath to keep it warm, and removing the paraffin from the structured flexible polymer with high water content by utilizing the principle that the paraffin melts at high temperature and separates from the water, thereby obtaining a structured flexible polymer with a specific designed structure;
[0060] When using a water bath for heat preservation, the temperature setting should be higher than 65°C and lower than 100°C. In this embodiment, the temperature setting is 75°C.
[0061] Step 9, preparation of structured flexible polymer porous structure: placing the structured flexible polymer prepared in step 8 into an oven and drying at high temperature until the water in the structured flexible polymer is completely evaporated and the total mass remains unchanged;
[0062] When using an oven to dry the moisture in the structured flexible polymer at high temperature, the temperature setting should be higher than 100° C., which is 100° C. in this embodiment; the minimum structure rod diameter of the prepared structured flexible polymer can reach 150 μm;
[0063] Step 10. Preparation of flexible piezoresistive sensor: evenly spin-coat conductive silver paste as electrode on the flexible substrate, and then adhere two electrodes to both sides of the structured flexible polymer porous structure prepared in step 9, heat and cure at 80°C for 10 minutes to form a flexible piezoresistive sensor.
[0064] Figure 2 This is the SEM image of the structured porous flexible polymer prepared in Example 1. Figure 2 It can be seen that the designable three-dimensional structure molding and manufacturing of porous flexible polymers is achieved by utilizing the indirect 3D printing process based on soluble photosensitive resin. The prepared porous flexible polymer has a complex and complete three-dimensional structure, which shows that the method of the present invention has good three-dimensional structure molding ability.
[0065] Figure 3 This is a SEM image of a microrod of a structured porous flexible polymer prepared in Example 1. Figure 3 It can be seen that by using water as a template, a large number of micron-sized pores can be further introduced into the structured flexible polymer, and the minimum rod diameter of the prepared structure can reach 150 μm, which demonstrates the cross-scale manufacturing capability of the method of the present invention.
[0066] Figure 4 This is a cross-sectional SEM image of the structured porous flexible polymer prepared in Example 1. Figure 4 It can be seen that the CNTs are evenly distributed in the prepared structured porous flexible polymer, which indicates that the porous flexible polymer manufactured by the method of the present invention has good electrical conductivity.
[0067] Figure 5 The piezoresistive signal curve of the flexible piezoresistive sensor prepared in Example 1 is shown in FIG. Figure 5It can be seen that under small strain, the resistance of the sensor changes linearly with the strain, and the sensitivity GF can reach 8.34, which shows that the flexible piezoresistive sensor manufactured by the method of the present invention has a high sensitivity; at the same time, under large strain, the resistance of the sensor can still change linearly with the strain, and the strain can reach about 65%, and the resistance change rate reaches 99.5%, which shows that the flexible piezoresistive sensor manufactured by this manufacturing method has a wide stress response range and can realize pressure signal detection under large strain.
Claims
1. A cross-scale manufacturing method for a porous flexible piezoresistive sensor with a designable structure, characterized in that: The following steps are involved: The first step is to disperse the conductive filler in the flexible polymer phase: add a surfactant to an organic solvent and stir to dissolve it, with a mass fraction of 1%-20%, disperse the conductive filler in the organic solvent, with a mass fraction of 0.5%-10%, use a cell disruptor to evenly disperse the conductive filler in the organic solvent, and then mix the organic solvent dispersed with the conductive filler with the flexible polymer in a mass ratio of 1:2 to 2:1, heat in a water bath and stir with a magnetic stirrer to fully mix them, and dry the organic solvent to obtain a flexible polymer dispersed with the conductive filler; Step 2, preparation of a flexible polymer-water emulsion: adding a flexible polymer curing agent to the flexible polymer dispersed with a conductive filler prepared in the first step and stirring to fully mix, then slowly adding deionized water to the flexible polymer and stirring to fully obtain a uniform flexible polymer-water emulsion; The third step is to prepare the soluble photosensitive resin mold: pour the soluble photosensitive resin into the resin tank of the light-curing 3D printer, adjust the position of the printing work platform and the release film until the light machine is fully focused, set the process parameters of 3D printing layer thickness, exposure time and light intensity on the 3D printer host, and use ultraviolet light exposure to realize the layer-by-layer curing and stacking of the resin mold to prepare a soluble photosensitive resin mold with a structural design; Step 4, preparation of a paraffin mold: placing a paraffin block into a first container, placing the first container into a vacuum oven and heating it until the paraffin is completely melted, then placing the soluble photosensitive resin mold prepared in the third step into the melted paraffin until the paraffin completely immerses the soluble photosensitive resin mold, then evacuating the container so that the paraffin can completely wrap the soluble photosensitive resin mold, and cooling the container until the paraffin is completely cooled and solidified; Step 5, removing the soluble photosensitive resin: placing the paraffin mold wrapped with the soluble photosensitive resin mold prepared in step 4 into an alkaline solution until the photosensitive resin is completely dissolved in the alkaline solution, and using a liquid convection device to assist in dissolving the photosensitive resin; Step 6, pouring the flexible polymer-water emulsion into the paraffin mold: placing the paraffin mold obtained in the fifth step into the flexible polymer-water emulsion prepared in the second step, so that the emulsion completely immerses the paraffin mold, evacuates to remove the residual air in the emulsion, and leaves it to stand until the emulsion is completely poured into the paraffin mold; Step 7, curing of the flexible polymer-water emulsion: placing the paraffin mold filled with the flexible polymer-water emulsion obtained in step 6 into an oven for curing so that the flexible polymer is completely cross-linked and solidified; Step 8, removing the paraffin mold: placing the structured flexible polymer wrapped with paraffin prepared in step 7 into a second container filled with water, and placing the second container in a water bath to keep it warm, and utilizing the principle that paraffin melts at high temperature and separates from water to remove the paraffin from the structured flexible polymer with high water content, thereby obtaining a structured flexible polymer with a specific designed structure; Step 9, preparation of structured flexible polymer porous structure: placing the structured flexible polymer prepared in step 8 into an oven and drying at high temperature until the water in the structured flexible polymer is completely evaporated and the total mass remains unchanged; Step 10. Preparation of flexible piezoresistive sensor: evenly spin-coat conductive silver paste as electrodes on the flexible substrate, and then adhere two electrodes to both sides of the structured flexible polymer porous structure prepared in step 9, heat and cure, to form a flexible piezoresistive sensor.
2. The method according to claim 1, characterized in that: In the first step, the flexible polymer material is polydimethylsiloxane (PDMS); the organic solvent is one or more of anhydrous ethanol, tert-butyl alcohol, isopropanol, n-hexane, and toluene; the conductive filler is one or more of carbon nanotubes, carbon nanosheets, MXene, and graphene. When carbon nanotubes are used, long-walled multi-walled carbon nanotubes with a length of 10-30 μm, an inner diameter of 5-10 nm, and an outer diameter of 20-30 nm are used; the surfactant is one or more of sodium dodecyl sulfate (SDS), benzalkonium chloride (BKC), TritonX-100 (TX-100), dimethylsiloxane ethylene oxide block copolymer (DBE-621), and Span80.
3. The method according to claim 1, characterized in that In the second step, the method of slowly adding water to the flexible polymer is as follows: slowly adding small doses to the flexible polymer uniformly dispersed with the conductive filler prepared in the first step, and stirring for 1-2 minutes using a planetary centrifugal mixer after each addition of water. After all the water is added to the flexible polymer, stirring for 15-25 minutes using a planetary centrifugal mixer to fully mix the flexible polymer and water to obtain a stable flexible polymer-water emulsion; when gradually adding small doses of water, the single dripping amount shall not exceed 10% of the total mass of the flexible polymer; When the flexible polymer is mixed with deionized water, the mass proportion of the deionized water is 10% to 70%; when a planetary centrifugal mixer is used for stirring, the speed setting range is 200rpm to 2000rpm.
4. The method according to claim 1, characterized in that: In the fifth step, the alkali solution is one or both of KOH solution and NaOH solution; and the liquid convection device is a small water pump or a similar device.
5. The method according to claim 1, characterized in that: When the flexible polymer-water emulsion is heated in the seventh step to crosslink and solidify it, the oven temperature should be set below 60°C.
6. The method according to claim 1, characterized in that: In the eighth step, the temperature setting of the water bath for heat preservation should be higher than 65°C and lower than 100°C.
7. The method according to claim 1, characterized in that: In the ninth step, the temperature setting of using an oven to dry the moisture in the structured flexible polymer at high temperature should be higher than 100°C.
8. The method according to claim 1, characterized in that: The minimum structural rod diameter of the structured flexible polymer porous structure prepared in the ninth step reaches 150 μm.
Citation Information
Patent Citations
3D printing self-filling multi-level porous sensor and preparation method thereof
CN114211744A
Porous nano composite material for self-energized self-sensing flexible electronic device and preparation method and application of porous nano composite material
CN115386131A